2018
DOI: 10.1186/s12917-018-1590-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and dissemination of antimicrobial-resistant Salmonella in broiler farms with or without enrofloxacin use

Abstract: BackgroundSalmonella is a major zoonotic food-borne pathogen that persists on poultry farms, and animals undergo reinfection with endemic strains. The present study aimed to investigate the characteristics and dissemination of antimicrobial-resistant Salmonella within and between broiler farms that used enrofloxacin and those that did not.ResultsCloacal and environmental (litter, feed, and water) samples from two selected flocks in each of 12 farms owned by the same company were collected three times over a 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 55 publications
4
26
3
Order By: Relevance
“…The highest levels of resistance manifested by the isolates from the aforementioned studies were against tetracycline (100%), ampicillin (100%), clindamycin (100%), and ciprofloxacin (83%). Moreover our Salmonella isolates were susceptible to ciprofloxacin in contrast to that reported elsewhere as being between 30.8% and 96% [ 28 , 29 , 30 , 31 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The highest levels of resistance manifested by the isolates from the aforementioned studies were against tetracycline (100%), ampicillin (100%), clindamycin (100%), and ciprofloxacin (83%). Moreover our Salmonella isolates were susceptible to ciprofloxacin in contrast to that reported elsewhere as being between 30.8% and 96% [ 28 , 29 , 30 , 31 ].…”
Section: Discussioncontrasting
confidence: 99%
“…These findings further support the role of the environment in the dissemination and recirculation of MDR Salmonella [ 49 , 50 ]. Shang et al (2018) found a significantly higher isolation rate of MDR Salmonella from litter samples compared to other samples in broiler farms, indicating the significance of poultry litters in the in-door environmental transmission of MDR Salmonella [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic sensitivity test results presented in table 6 showed that some human isolates are 100% resistant to certain antibiotics such as neomycin and chloramphenicol, despite their limited use in the human field. This finding illustrates the pivotal role of poultry farms in transmitting the infection to humans (Shang et al, 2018). The results of the antibiotic sensitivity test suggested the guidelines for both physicians and veterinarians to select the relevant antibiotics to diminish antibiotic resistance among NTS which have industrial and public health significance.…”
Section: Discussionmentioning
confidence: 74%
“…In 2016, the use of colistin sulfate as a performance enhancer was banned in Brazil (Brasil, 2016) in order to prevent cross-resistance of pathogens of public health concern (Hu et al, 2017). Therefore, the identification of polymyxin E-resistant zoonotic Salmonella strains in layer farms in the present study is a matter of concern, as this drug is one of the last treatment choices for human salmonellosis, and resistance against broad-spectrum drugs may result in high mortality rates (Costa et al, 2013;Shang et al, 2018).…”
Section: Resultsmentioning
confidence: 91%
“…The 41% rate of ciprofloxacinresistant strains determined in the present study is in agreement with previous studies, which also found high incidence rates of resistant Salmonella spp., of 25.0% in Ghana (Andoh et al, 2017) and of 35.1% in Shanghai (Wei et al, 2019). These results are a matter of concern, as the emergence of such strains may lead to failure of the treatment of severe bacterial infections in human medicine (Costa et al, 2013;Shang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%